Two different origins of the Q-slope problem in superconducting niobium film cavities for a heavy ion accelerator at CERN - A. Miyazaki; W. Venturini Delsolaro (Physical Review Accelerators and Beams, 2019)
Superconducting niobium film cavities deposited on copper substrates (Nb/Cu) have suffered from strong field-dependent surface resistance, often referred to as the Q-slope problem, since their invention. We argue that the Q-slope may not be an intrinsic problem, but rather originates from a combination of factors which can be revealed in appropriate environmental conditions. In this study, extrinsic effects were carefully minimized in a series of experiments on a seamless cavity. The origin of the Q-slope in low frequency cavities is traced back to two contributions with different temperature and magnetic field dependences. The first component of Q-slope, affecting the residual resistance, is caused by trapped magnetic flux which is normally suppressed by a magnetic shield for bulk niobium cavities. The second, temperature dependent component of Q-slope, is similar to the medium-field Q-slope which is well known in bulk niobium cavities. These results are compared with theoretical models and possible future studies are proposed.